Description of a new species of Hisonotus (Loricariidae: Siluriformes) from rio Araguaia basin - Ribeiro-Silva, Luís R.; Silva, Gabriel S. C.; Venere, Paulo C.; Da Silva, Hugmar Pains; Roxo, Fábio F. (Zootaxa, 2020)
A new species of Hisonotus is described from headwaters of rio Araguaia basin, municipality of Barra do Garças, Mato Grosso state, Brazil. The new species is distinguished from its congeners by a V-shaped spinelet, yellowish teeth, absence of unpaired platelets at typical adipose fin position, the caudal-fin color hyaline with three transverse dark bars, one abdominal median plate series, and by morphometric and meristic characters.